2011
DOI: 10.2478/s11536-011-0061-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is related to worse emotional state

Abstract: AbstractThe aim was to evaluate vitamin D levels in young healthy Lithuanian males in winter and to find possible associations of vitamin D concentration to body composition, cognitive functioning, emotional state.Subjects and Methods A total of 130 healthy males (age range, 18–26 years) were divided into the subgroups according to vitamin D concentration. The Profile of Mood States (POMS) questionnaire and Hospital Anxiety and Depression Scale were employed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…14 The authors demonstrated no difference in SES in high and low vitamin D groups. 14 For the studies that presented education across vitamin D groups, the majority (n = 10) 9,13,14,18,37,44,48-50,52 also observed no difference in level of education between high and low vitamin D, while seven studies 7,11,12,15,28,33,51 did report lower education in participants with low vitamin D. Two studies 34,35 performed no covariate adjustment. Most studies (n = 32) performed multivariate adjustments and four studies performed partial adjustments for at least age and education.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…14 The authors demonstrated no difference in SES in high and low vitamin D groups. 14 For the studies that presented education across vitamin D groups, the majority (n = 10) 9,13,14,18,37,44,48-50,52 also observed no difference in level of education between high and low vitamin D, while seven studies 7,11,12,15,28,33,51 did report lower education in participants with low vitamin D. Two studies 34,35 performed no covariate adjustment. Most studies (n = 32) performed multivariate adjustments and four studies performed partial adjustments for at least age and education.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…30,32 Most studies were mixed gender, two included only women 13,33 and five were male only. 16,18,[34][35][36] While the majority (n = 25) of studies recruited older adults, five investigated middle aged adults, 14,29,32,34,35 and 11 included both. 5,7,8,16,27,[36][37][38][39][40][41] Eight studies reported vitamin D as a continuous variable, 5,6,10,27,29,36,39,42 27 as a categorical variable, and three reported both.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations